Experimental Investigation on the Stability of 40% Ethylene Glycol Based TiO2-Al2O3 Hybrid Nanofluids - Urmi, Wajiha Tasnim; M. M., Rahman; Azmi, W. H.; K., Kadirgama; D., Ramasamy; Maleque, M. A. (Akademia Baru Publishing (M) Sdn Bhd, 2020)
This paper is presented to investigate experimentally on the stability of 40% ethylene glycol-based TiO2-Al2O3 hybrid nanofluids. Recently, the research is more highlighted on the thermophysical-properties of nanofluids. Hence, the stability of the hybrid nanofluids thoroughly assessed in this research work. The study uses the two-step method for preparing 40% ethylene glycol-based TiO2-Al2O3 hybrid nanofluids. The experiment is carried out for the various combination of mixture ratios including 20:80, 40:60, 50:50, 60:40 and 80:20 of TiO2-Al2O3 nanoparticles with a volume concentration of 0.1%. The stability assessment of hybrid nanofluids is accomplished through visualisation effect, transmission electronic microscopic observation, UV-Vis spectrophotometry and zeta potential value from particle size analyser. The findings show the optimum mixing ratios of TiO2-Al2O3 nanoparticles in terms of stability which is further confirmed by Zeta potential and absorbency from UV-Vis spectrophotometry. The results from the study reveal that 80:20 ratio of TiO2-Al2O3 nanoparticles possesses the best uniformity for over 21 days without any noticeable settlement of particles in the colloidal suspension. Moreover, 50:50 and 60:40 ratios show modest stability for almost two weeks while 20:80 and 40:60 ratios of TiO2-Al2O3 nanoparticles show minimum stability along with rapid sedimentation in the dispersion. However, it is also evident that the optimum mixing ratio of TiO2-Al2O3 hybrid nanofluids has excellent stability which will lead to further study on the thermal properties of nanofluids and finally motivate engineers to the real-life application of nanofluids.